In Vitro Propagation of Albizia Lebbeck Through Axillary Bud Culture - Al-Joboury, K.R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present study describes a protocol for rapid in vitro micropropagation of Albizia lebbeck during the period of October 2007 to October 2009 through nodal segments containing axillary buds. The buds induced to produce a large number of multiple shoots by culturing on MS medium supplemented with different concentrations of BA (benzyladenine) and NAA (Î±-naphthalene acetic acid). The maximum number of shoots per explants was obtained on MS medium supplemented with 1.0 mg/L BA and 0.1 mg/L NAA was (4.8) after 4 weeks of culture. Excised shoots were rooted on half strength MS medium fortified with 0.5 mg/L either IBA (indolbutyric acid) or NAA alone. The complete plantlets thus obtained were successfully transferred to soil.